Acute cardiac tamponade - Mesa, Guillermo; Vidal, Hugo; Abisab, Odel; Varela, José A; Larre Borges, Uruguay (Cirugía del Uruguay, 1973)
In an experimental study of the treatment of acute cardiac tamponade through evacuation of the pericardial contents, cardiocentesis is classificied as a valuable tool complementing the final surgical treatment.